PEMBELAJARAN INOVATIF KIMIA DASAR YANG MENYENANGKAN - Elfira Rosa Pane (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Learning chemistry is boring for most students when it is delivered and tended to overwhelm students. This paper aims at providing an innovative alternative to learning in general chemistry subjects.